A usability study of two formats of a shortened systematic review for clinicians. Issue 12 (23rd December 2014) - Perrier, Laure; Kealey, M Ryan; Straus, Sharon E
Abstract : Objective: The aim of this study was to evaluate the usability of two formats of a shortened systematic review for clinicians. Materials and methods: Usability of the prototypes was assessed using three cycles of iterative testing. 10 participants were asked to complete tasks of locating information or items within two prototypes and 'think aloud' while being audio taped. Interviews were also audio recorded and participants completed a systematic usability scale. Results: Revisions were made between each iteration in order to address issues identified by participants. Finding information relating to the number of studies in the meta-analysis, and locating the number of studies in the entire systematic review were revealed as areas needing attention during the usability evaluation. Conclusions: Iterative testing combined with a multifaceted approach to usability testing offered essential insight into aspects of the prototypes that required modifications. Alterations were made in order to create finalised versions of the two shortened systematic review formats.